Fishes of West Bengal: Review and Annotated Checklist - Sen , Arya; Sreeraj , Chemmencheri Ramakrishnan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
An updated systematic inventory of the fish faunal variety from the state of West Bengal, comprising 894 species represented by 36 orders and 152 families, has been produced following an extensive review of the literature. Diversity-wise, order Acanthuriformes, has 19 families and 120 species, is the top order of both freshwater and marine fishes. Cypriniformes, which has 7 families and 117 species, is the second most diverse order and the most diverse order in freshwater. Cyprinidae, makes up 6% of the entire fish population in West Bengal, is the family with the most diversity. Marine fishes showed the highest diversity in Gobiidae and Carangidae with 5.6% and 4.8% respectively. 221 species are fully freshwater species, whereas 297 species are marine. The rest of the species are associated with fresh water, brackish and marine habitats. According to the IUCN red list status, 8 species belong to the critically endangered category, 18 belong to the endangered category, 30 species belong to the vulnerable category and 37 species belong to the near threatened category. The conservation status of 239 fish species found in West Bengal has not yet been determined by IUCN. The present study is the first attempt to provide a comprehensive data of fish faunal diversity occurring from all the habitats present in West Bengal, which will ultimately help in the management of the prospects of fisheries resources from West Bengal as well as provide support for the effective conservational planning process.